A review of Hyphodiscaceae - Quijada L.; Baral H.O.; Johnston P.R.; Pärtel K.; Mitchell J.K.; Hosoya T.; Madrid H.; Kosonen T.; Helleman S.; Rubio E.; Stöckli E.; Huhtinen S.; et al. (Westerdijk Fungal Biodiversity Institute, 2025)
In a recently published classification scheme for Leotiomycetes, the new family Hyphodiscaceae was erected; unfortunately, this study was rife with phylogenetic misinterpretations and hampered by a poor understanding of this group of fungi. This manifested in the form of an undiagnostic familial description, an erroneous familial circumscription, and the redescription of the type species of an included genus as a new species in a different genus. The present work corrects these errors by incorporating new molecular data from this group into phylogenetic analyses and examining the morphological features of the included taxa. An emended description of Hyphodiscaceae is provided, notes and descriptions of the included genera are supplied, and keys to genera and species in Hyphodiscaceae are supplied. Microscypha cajaniensis is combined in Hyphodiscus, and Scolecolachnum nigricans is a taxonomic synonym of Fuscolachnum pteridis. Future work in this family should focus on increasing phylogenetic sampling outside of Eurasia and better characterising described species to help resolve outstanding issues.